2015
DOI: 10.2106/jbjs.cc.n.00024
|View full text |Cite
|
Sign up to set email alerts
|

Checkrein Deformity Associated with Intra-Articular Talar Fracture

Abstract: Physicians should suspect the entrapment of the FHL tendon in cases of flexion deformity of the hallux associated with talar fracture. Proper examination of the forefoot when a patient presents with a hindfoot injury will help to avoid missing such deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Checkrein deformity of the great toe secondary to entrapment of the flexor hallucis longus tendon has been described after fractures of the talus and ankle and after fibular graft removal. 30 - 32 Similar to our case, Tucker et al 33 noticed slight plantar flexion of the toes at the metatarsal-phalangeal and interphalangeal joints after a closed, lateral subtalar joint dislocation. However, a checkrein deformity was not diagnosed in this case.…”
Section: Discussionsupporting
confidence: 86%
“…Checkrein deformity of the great toe secondary to entrapment of the flexor hallucis longus tendon has been described after fractures of the talus and ankle and after fibular graft removal. 30 - 32 Similar to our case, Tucker et al 33 noticed slight plantar flexion of the toes at the metatarsal-phalangeal and interphalangeal joints after a closed, lateral subtalar joint dislocation. However, a checkrein deformity was not diagnosed in this case.…”
Section: Discussionsupporting
confidence: 86%
“…The FHL tendon distinctively functions to flex the great toe, and tethering of the tendon can lead to flexion contracture of the interphalangeal joint of the big toe, a finding known as the checkrein deformity 5,6 . Abolfotouh et al reported 3 cases of FHL entrapment with subsequent checkrein deformities in the setting of talus fractures 5 . On the other hand, Anglen and Gehrke reported entrapment of the FHL tendon from a calcaneus fracture, with no checkrein deformity on physical examination 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The flexor hallucis longus (FHL) tendon courses through the groove between the medial and lateral tubercules of the posterior process of the talus, making it vulnerable to displacement in complex fractures 2 . Two reports in the literature have reported this complication in talar body fractures 5,6 . If left untreated, the FHL can tether to the fracture site resulting in a malreduced talus with subsequent malunion, as well as tenosynovitis and restrictive hallux extension 5,6 .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…13 15 Checkrein deformities have also been described in talar fractures and in one reported case of an open lateral subtalar joint dislocation. 16,17 To our knowledge this is the first case that describes an open TTD with a checkrein deformity of the hallux without extrusion of the talus. This case presents two uncommon deformities, their acute management as well as the long term follow up.…”
Section: Introductionmentioning
confidence: 87%